2017
DOI: 10.1158/1078-0432.ccr-16-1946
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling of Patient-Derived Xenografts for Lung Cancer Identifies B2M Inactivation Impairing Immunorecognition

Abstract: We aimed to maximize the performance of detecting genetic alterations in lung cancer using high-throughput sequencing for patient-derived xenografts (PDXs). We undertook an integrated RNA and whole-exome sequencing of 14 PDXs. We focused on the genetic and functional analysis of β2-microglobulin (B2M), a component of the HLA class-I complex. We identified alterations in genes involved in various functions, such as involved in immunosurveillance. We extended the mutational analysis of to about 230 lung cancers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 37 publications
3
45
0
5
Order By: Relevance
“…Finally, we note that transcript abundance for the B2M gene encoding beta-2 microglobulin has one of the most negative hazard coefficients, likely reflecting its role in MHC class I antigen presentation of neo-antigens to CD8 T cells and consistent with recent reports of the importance of this process for immune control of tumors [54]. Further, a truncation mutant of B2M can confer resistance to PD-1 blockade in melanoma [55], and mutations in B2M have been shown to disrupt immune surveillance in lung cancer [56]. The large negative hazard coefficient associated with HAPLN3, encoding a hyaluronan and proteoglycan link protein, suggests that this gene may warrant further investigation in the context of immune recognition and targeting.…”
Section: Cutaneous Melanoma Is Generally Associated With a Strong Immsupporting
confidence: 80%
“…Finally, we note that transcript abundance for the B2M gene encoding beta-2 microglobulin has one of the most negative hazard coefficients, likely reflecting its role in MHC class I antigen presentation of neo-antigens to CD8 T cells and consistent with recent reports of the importance of this process for immune control of tumors [54]. Further, a truncation mutant of B2M can confer resistance to PD-1 blockade in melanoma [55], and mutations in B2M have been shown to disrupt immune surveillance in lung cancer [56]. The large negative hazard coefficient associated with HAPLN3, encoding a hyaluronan and proteoglycan link protein, suggests that this gene may warrant further investigation in the context of immune recognition and targeting.…”
Section: Cutaneous Melanoma Is Generally Associated With a Strong Immsupporting
confidence: 80%
“…Moreover, since genetic defects in antigen processing machinery genes have been found in ~5% of lung cancers and have been linked to reduced survival upon treatment with immune checkpoint inhibitors (25,43), the contribution of this pathway to primary resistance in lung cancer should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, multiple clinical reports and subsequent experiments have confirmed that B2M alterations in tumor cells (i.e., mutations, deletions, and down-regulation) can largely induce acquired CPI resistance ( Gettinger et al, 2017 ; Janjigian et al, 2017 ; Grasso et al, 2018 ). Importantly, high frequency of initial B2M mutations were found in patient-derived xenografts for lung cancer, suggesting patients with this gene mutation may experience primary resistance to CPIs ( Pereira et al, 2017 ). With CRISPR screening, multiple genes were also identified to be essential for cancer immunotherapy, including APLNR , which can interact with JAK1 ( Patel et al, 2017 ).…”
Section: Tumor Autonomous Mechanismsmentioning
confidence: 99%